Microbiological, Nutritional and Sensory Characteristics of the Foodstuff “Foura” Produced From Millet in Benin - TCHEKESSI, C. K. Célestin; Badoussi, Marius Eric; Mousse, Yabo Faoziath; Djogbe, Aurelle Anayce; GANDEHO, Gamèli Justin; Banon, S. B. Jultesse; SACHI, Amour Pivot; Choucounou, Ornella Ingrid; Bokossa Yaou, Innocent; AGBANGLA, CLÉMENT (My University, 2021)
Objective: The objective of study was to develop a good quality “Foura” in order to ensure the safety of consumers. Materials and Methods: A survey was conducted in the districts of Cotonou, Kandi and Malanville which are considered to be areas of high production and consumption of “Foura”. Microbiological, nutritional and sensory analysis were carried out of the unfermented “Foura” sold on the market and the fermented and unfermented “Foura” that we produced. A sensory analysis was performed after production. Results: The results of the survey showed that the production technology of the “Foura” is dependent on the empirical knowledge of the producers. Microbiological analysis revealed that unfermented “Foura” sold in the market contained thermotolerant coliforms, E. coli, yeasts, sulphite-reducing bacteria in excess of set limit values. On the other hand, the unfermented and the fermented “Foura” that we produced are of satisfactory hygienic quality because they do not contain thermotolerant coliforms, ASR, or E. coli. Nutritional analysis showed that unfermented “Foura” sold in market and the unfermented one produced contained proteins (3.77 and 2.81%), total sugars (3.29 and 2.82%), fats (5.08 and 4.23%), iron (2.10 and 2.71 mg) and an energy value (73.96 kcal/100 g and 60.5 kcal/100 g) respectively. However, the fermented “Foura” is richer in iron (3.09 mg) protein (7.13%), fat (5.93%), energy value (90.85 kcal/100 g) and more appreciated by the tasters. Conclusion: Fermented and non-fermented "Foura" produced from millet are rich in nutrients and provide the body with a very appreciable energy value.
Keywords: Millet; milk; fermentation; "Foura"; nutritional quality; cassava processing; complementary food